Carbazole-based bis-imidazole ligand-involved synthesis of inorganic–organic hybrid polyoxometalates as electrochemical sensors for detecting bromate and efficient catalysts for selective oxidation of thioether. Issue 8 (3rd February 2022) - Wang, Xiang; Lin, Jiafeng; Li, Huan; Wang, Chenying; Wang, Xiuli
Abstract : Three inorganic–organic hybrid polyoxometalates were prepared using a bis-imidazole ligand featuring carbazole as a connector, exhibiting not only diverse structures, but also good electrochemical sensing activities for bromate, as well as efficient catalytic performances for oxidation of thioether. Abstract : Considering the potential application on preparing electrode and catalyst materials of inorganic–organic hybrid polyoxometalates, a bis-imidazole ligand with carbazole as a connector, 3, 6-di(1H-imidazol-1-yl)-9H-carbazole (L), was used for preparing inorganic–organic hybrid polyoxometalates. As a result, three complexes formulated by [NiL2 (Mo2 O7 )] (1 ), [Cu(H2 O)2 (HL)2 (β-Mo8 O26 )]·H2 O (2 ) and [Ni2 (H2 O)4 L2 (CrMo6 (OH)5 O19 )]·6H2 O (3 ) were obtained successfully. Structural analysis indicated that the different polyoxoanions and metal ions showed important influences on the formation of structures. In the presence of Ni 2+ ions and heptamolybdate, a 2D network constructed from Ni 2+ ions and L ligands was formed in complex 1, in which the [Mo4 O14 ] 4− polyoxoanions were encapsulated. But the use of Cu 2+ ions led to a 1D chain of complex 2, which was composed of [β-Mo8 O26 ] 4− polyoxoanions and mononuclear CuL2 units. By utilizing [CrMo6 (OH)5 O19 ] 4− as the inorganic building block, complex 3 showed a 2D (4, 4)-connected layer. Complexes 1–3 could be employed as electrode materials for sensing bromate with the limits of detection of 0.315 μM for 1, 0.098 μM for 2 and 0.551 μM for 3 . Moreover, these complexes showed efficient catalytic activity for the selective oxidation of thioethers.